Suppression of exchange bias effect in maghemite nanoparticles functionalized with H2Y - Guivar J.A.R. (2016)
The structural, vibrational, morphological and magnetic properties of maghemite (γ-Fe2O3) nanoparticles functionalized with polar molecules EDTA(or H4Y) and H2Y are reported. The samples were functionalized before and after total synthesis of γ-Fe2O3 nanoparticles. The molecules are anchored on the monodentate mode on the nanoparticles surface. Transmission electron microscopy (TEM) revealed the formation of maghemite nanoparticles with small diameter of 4 nm for the sample functionalized upon synthesis and 7.6 and 6.9 nm for the samples functionalized with EDTA and H2Y after the formation of nanoparticles. Exchange bias phenomena were observed in some of the samples functionalized with EDTA at temperatures below 70 K. The presence of the bias effect was discussed in terms of the formation of a thin layer of a secondary phase like lepidocrocite, and the absence of this effect was explained in terms of the chemisorption of carboxylic groups from EDTA which suppressed the canting. Studies of Mössbauer spectroscopy as a function of temperature showed slow relaxation effects and allowed discussion of the secondary phase. In the M-T curves a maximum around 116 K was associated with this secondary phase also in agreement with the Mössbauer studies. The dynamic properties were studied by AC susceptibility, the out of phase signal revealed a spin glass like regime below 36.5 K.